Physical fitness of the top judoists in Japan - Sasa, T.; Shinozuka, T.; Kato, N.; Matsumoto, Y.; Ogawa, S.; Morita, S.; Akutsu, K.; Ikai, M.; Ishiko, T.; Yamakawa, J.; Asami, T.; Tomiki, K.; et al. (Association for the Scientific Studies on Judo, Kodokan, 1961)
The general tendency of the sports world, recently, is to adopt a rational and efficient hard training method based on the principles of anatomy, physiology, psychology, dynamics and other Sciences, instead of the old and irrational empirical method. On the request of the late Jigoro Kano, founder of the Kodokan, Prof. Seizaburo Uramoto, in 1930, undertook to make a scientific study of " Shizentai" (Natural posture) and "Jigotai" (Defensive Posture). This was the first of a series of scientific studies on physicai fitness in relation to Judo.